2000
DOI: 10.1080/026999300402763
|View full text |Cite
|
Sign up to set email alerts
|

Beyond valence: Toward a model of emotion-specific influences on judgement and choice

Abstract: Most theories of affective in¯uences on judgement and choice take a valencebased approach, contrasting the effects of positive versus negative feeling states. These approaches have not speci® ed if and when distinct emotions of the same valence have different effects on judgement. In this article, we propose a model of emotion-speci® c in¯uences on judgement and choice. We posit that each emotion is de® ned by a tendency to perceive new events and objects in ways that are consistent with the original cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

117
2,179
15
47

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 2,454 publications
(2,358 citation statements)
references
References 66 publications
117
2,179
15
47
Order By: Relevance
“…This possibility would conform with appraisal tendency theories of emotions (Lerner & Keltner, 2000;Smith & Ellsworth, 1985), according to which a person's emotional state leads to a specific cognitive appraisal of the environment and, in turn, to specific behavioral reactions. Cognitive appraisals are made along several dimensions, including perceived certainty (i.e., degree of subjective certainty about what is going on in the environment), situational control (i.e., degree to which a person feels the situation is controlled by circumstances versus by a human agent, including herself), and anticipated effort (i.e., degree to which a person feels that she needs to exert effort to deal with the situation).…”
Section: Emotion As Information and As Informational Regulatorsupporting
confidence: 57%
“…This possibility would conform with appraisal tendency theories of emotions (Lerner & Keltner, 2000;Smith & Ellsworth, 1985), according to which a person's emotional state leads to a specific cognitive appraisal of the environment and, in turn, to specific behavioral reactions. Cognitive appraisals are made along several dimensions, including perceived certainty (i.e., degree of subjective certainty about what is going on in the environment), situational control (i.e., degree to which a person feels the situation is controlled by circumstances versus by a human agent, including herself), and anticipated effort (i.e., degree to which a person feels that she needs to exert effort to deal with the situation).…”
Section: Emotion As Information and As Informational Regulatorsupporting
confidence: 57%
“…Other investigators recently proposed a similar "matching hypotheses" regarding the relations among rumination, forgiveness, and affect (Berry, Worthington, O'Connor, et al, 2005), and it comports well with other evidence that anger is associated with approach motivation (Harmon-Jones, Vaughn-Scott, Mohr, Sigelman, & Harmon-Jones, 2004) and optimistic appraisals of risk, whereas fear leads to pessimistic appraisals of risk (Lerner & Keltner, 2000.…”
Section: Anger and Fear: Two Possible Mediators Of The Rumination-forsupporting
confidence: 56%
“…Second, anxiety heightens self-focused attention (Easterbrook, 1959;Sarason, 1975), which itself can increase reliance on self-knowledge during social prediction (Fenigstein & Abrams, 1993). Third, anxiety is typically accompanied by a sense of uncertainty (Lazarus, 1991;Lerner & Keltner, 2000;Smith & Ellsworth, 1985), which itself is associated with greater reliance on accessible knowledge during judgment (Mussweiler & Strack, 2000;Tversky & Kahneman, 1974). Indeed, studies have found that enduring stressful, anxiety-inducing events-and the subjective experience of uncertainty that accompanies such events-can increase reliance on self-generated numeric anchors (Inbar & Gilovich, 2011; see also Kassam, Koslov, & Mendes, 2009).…”
Section: Anxiety and Mental-state Reasoningmentioning
confidence: 99%
“…Building on these classic appraisal theories, Lerner and Keltner (Han, Lerner, & Keltner, 2007;Lerner & Keltner, 2000 This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Mental-state Reasoningmentioning
confidence: 99%